2009
DOI: 10.1016/j.jus.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease (NAFLD) in nonobese patients with diabetes: Prevalence and relationships with hemodynamic alterations detected with Doppler sonography

Abstract: Aim: To evaluate the prevalence, severity, and hemodynamic features of nonalcoholic fatty liver disease (NAFLD) in nonobese diabetics. Methods: We studied 100 consecutive nonobese (body mass index [BMI] < 30) patients with type 1 (n Z 17) or type 2 (n Z 83) diabetes and no known causes of liver disease. Steatosis was diagnosed and graded with ultrasonography. Digital sonographic images of the liver and right kidney were analyzed with dedicated software (HDI-Lab), and the liver/kidney ratio of grey-scale intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
(20 reference statements)
3
12
0
Order By: Relevance
“…Nontriphasic flow was appreciated in patients with increased liver echogenicity. 15 This result is also in concordant with previous observations. Although HARI and HAPI is not calculated in this study, some international studies suggests that these parameters were significantly greater in patients with moderate or severe inflammation than those with mild inflammation in controlled studies.…”
Section: Discussionsupporting
confidence: 93%
“…Nontriphasic flow was appreciated in patients with increased liver echogenicity. 15 This result is also in concordant with previous observations. Although HARI and HAPI is not calculated in this study, some international studies suggests that these parameters were significantly greater in patients with moderate or severe inflammation than those with mild inflammation in controlled studies.…”
Section: Discussionsupporting
confidence: 93%
“…Data of previous studies suggest that clues of AST aspartate aminotransferase, ALT alanine aminotransferase * Student T test steatohepatitis in NAFLD patients can be an increase in portal vein diameter, reduction of portal vein velocity, large splenic area, and an increase in RI of splenic artery [10,15,16]. In our baseline, similar characteristics were found in NAFLD patients with severe fatty liver disease (Table 2).…”
Section: Discussionsupporting
confidence: 81%
“…Although the traditional ultrasound (US) is an excellent diagnostic technique to reveal the presence of diffuse fatty liver disease, it is neither sensitive nor specific to reveal fibrosis, except in advanced stages where signs of cirrhosis are evident. Previous studies have demonstrated that hepatic artery resistive index (HARI) is significantly altered in patients with NAFLD, with significant reduction of this parameter with increasing of severity of diffuse fatty liver disease [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A study of 17 patients with type 1 diabetes aged 65 ± 7 years detected hepatic steatosis in 24% of them, noting that patients with fatty livers had higher body mass indexes than their counterparts without steatosis [73]. Targher et al observed fatty liver in 44.4% of a sample of 202 type 1 diabetes patients.…”
Section: Prevalence Of Nafld In Type 1 Diabetes Patientsmentioning
confidence: 98%